ENHANCING STUDENTS' SPEAKING FLUENCY THROUGH CONVERSATION PRACTICE: STUDENTS' VOICES - Wati, Dahlia; Kurniawan, Deni Endra; Nur Fadillah, Maratu Sholikhah; Ifadah, Muhimatul; Semilla, J-Roel B (Universitas Muhammadiyah Semarang, 2025)
Speaking fluency is a very important skill that must be mastered. Students' fluency in speaking can help them develop courage and confidence in interacting well with other people using English. This research aims to identify things that influence students' enthusiasm in conversation practice to improve their speaking proficiency. This research method is descriptive qualitative, using data collection techniques by distributing questionnaires to respondents to answer. The subjects of this research were second-semester students majoring in English education at Muhammadiyah University, Semarang. The results show that factors such as an interesting classroom atmosphere using practical practices that make the material interesting can increase students' enthusiasm in improving their speaking skills. This research provides important knowledge to create the development of more effective learning methods.